First rock magnetic and palaeomagnetic analyses of the Pre-Cenozoic rocks of the Velebit Mt. (Croatia) : prospects for applications in palaeogeographic and geotectonic studies - Lewandowski, Marek (Array, 2009)
Summary: Post-Carboniferous deposits of the Karst Dinarides were analyzed in terms of their palaeomagnetic and rock magnetic properties in order to identify the best sections for comprehensive palaeomagnetic studies on the geodynamic and palaeogeographic evolution of this mountain belt. A total of eighteen reconnaissance rock samples have been collected from the Permian red beds and dolomites, and Triassic, Jurassic, Cretaceous and Eocene carbonates. Most come from Velebit Mt., part of the Dinaric orogenic belt finally uplifted in the Oligocene–Miocene, and stretching NW–SE along the NE Adriatic coast. Experimental studies comprised identification of potential carriers of a natural remanent magnetization (NRM) by means of their properties of Curie temperature and coercivity accompanied by SEM and microprobe studies, demagnetization of standard palaeomagnetic specimens by means of alternating field and thermal cleaning, as well as the measurement and analysis of magnetic susceptibility and its anisotropy. Haematite (in Permian red beds) and Ti-magnetite (in carbonates) and sporadically goethite have been identified as remanence carriers. The state of preservation, ascertained by SEM observations, suggests a detrital origin of NRM in most of the samples. Characteristic NRM components (ChRM), both of high coercivity and unblocking temperatures, could be clearly identified in most of the specimens. These components show smeared distribution on the sphere and do not cluster around any known palaeomagnetic direction expected for the Velebit area from apparent polar wander paths, neither for Eurasia nor for Africa. This outcome suggests lack of overall remagnetization of the studied part of the Karst Dinarides after the last tectonic event and/or important contribution from tectonic rotations to the observed pattern of ChRM distribution